Programming logic and design comprehensive - Farrell, Joyce (Cengage Learning, 2015)
Prepares student programmers for success by teaching them the fundamental principles of developing structured program logic. This book offers a language-independent that approach to programming, with a distinctive emphasis on modern conventions.